Polymers, scaffolds and bioactive molecules with therapeutic properties in osteochondral pathologies: what's new?. (2nd August 2016) - López-Ruiz, Elena; Jiménez, Gema; García, María Ángel; Antich, Cristina; Boulaiz, Houria; Marchal, Juan Antonio; Perán, Macarena
ABSTRACT: Introduction : Despite clinical efforts, treatments to heal osteochondral lesions remain inefficient and frequently result, long-term, in joint arthroplasty. The complex structure of cartilage tissue, composed of a highly hydrated extracellular matrix (ECM), an avascular nature, and slow cellular turnover, hamper tissue regeneration after trauma or disease. Tissue engineering provides new promising alternatives to current treatments designed to regenerate osteochondral defects. Area covered : This review describes current and recent strategies of enhancing osteochondral repair through the use of cells, scaffolds, and bioactive molecules. Here, we review the latest (2011–2015) innovative patents in osteochondral regeneration, emphasizing novel strategies for articular cartilage repair. Finally, we present a summary of ongoing clinical trials that are testing innovative engineered products. Expert opinion : Promising tissue engineering based procedures have emerged as a therapeutic option for the treatment of osteochondral lesions. The development of multilayer scaffolds and the controlled release of bioactive molecules to promote in situ regeneration of both cartilage and bone are some of the latest technologies that intended to improve on the available traditional treatments. To confirm the potential of these novel approaches, long-term evaluation is necessary with special focus on studying the biological and mechanical proprieties of the synthesized tissues.